Spinal fusion of an unstable atlantoaxial fracture in a completely tetraplegic patient using silicate-substituted calcium phosphate - Putz, Cornelia; Wiedenhöfer, Bernd; Gerner, Hans-Jürgen; Hüttinger, Karl; Fürstenberg, Carl Hans (European journal of trauma and emergency surgery, 2010)
Bone graft harvesting from the iliac crest constitutes the gold standard in spinal surgery due to its osteogenic, osteoconductive and osteoinductive properties. Large amounts of autograft can provoke complications like donor site morbidity, pain and the need for a second operation. Therefore, research into bone graft substitutes is of great interest. Silicate-substituted calcium phosphate (ActifuseTM Synthetic Bone Graft, ApaTech Ltd, London) was used in combination with morselized corticocancellous graft in a transarticular stabilization (modified Magerl) of a completely tetraplegic patient with an unstable atlantoaxial fracture. Computed tomography showed bone bridging between the segment C1/C2, the surface of the implant and the remodeled bone at follow-up at 8 months. The use of silicate-substituted calcium phosphate as a bone graft extender in spinal surgery could be an alternative to autografting from the iliac crest. Vegetative symptoms are often underestimated but can be triggered by donor site morbidity or pain in patients after spinal cord injury.
Online veröffentlicht: 2. März 2009
Gesehen am 09.05.2023